Novel Lysine-Based Thioureas as Mechanism-Based Inhibitors of Sirtuin 2 (SIRT2) with Anticancer Activity in a Colorectal Cancer Murine Model - Farooqi, Ali Sohail (J Med Chem, 2019)
Sirtuin 2 (SIRT2) is a protein lysine deacylase that has been indicated as a therapeutic target for cancer. To further establish the role of SIRT2 in cancers, it is necessary to develop selective and potent inhibitors. Here, we report the facile synthesis of novel lysine derived thioureas as mechanism-based SIRT2 inhibitors with anticancer activity. Compounds AF8, AF10, and AF12 selectively inhibited SIRT2 with IC(50) values of 0.06, 0.15, and 0.08 μM, respectively. Compounds AF8 and AF10 demonstrated broad cytotoxicity amongst cancer cell lines, but minimal toxicity in noncancerous cells. AF8 and AF10 inhibited the anchorage-independent growth of human colorectal cancer cell line HCT116 with GI(50) values of ~7 μM. Furthermore, AF8 potently inhibited tumor growth in a HCT116 xenograft murine model, supporting that SIRT2 is a viable therapeutic target for colorectal cancer.